Global Welfare Agenda in Old Oil Well Management: A Maqāṣid Perspective and Jurisprudence of Equitable Energy - Raissa Soamanjary; Indah Febriani (Indonesian Journal of Law and Islamic Law (IJLIL), 2026)
This study examines the urgency of fulfilling the rights of masyarakat lingkar tambang (mining-ring communities) in the governance of old oil wells in Indonesia, focusing on Babat Toman, Batanghari Leko, and Bayung Lencir Subdistricts in Musi Banyuasin Regency, South Sumatra. It adopts a normative Islamic framework grounded in maqāṣid al-sharīʿah (objectives of Islamic law) and Muhammadiyah’s Jurisprudence of Equitable Energy. Employing a socio-legal qualitative approach, the study analyzes the intersection between regulatory frameworks, social justice, and Islamic ethical principles in natural resource governance. The findings reveal that, despite the existence of regulatory instruments such as Ministry of Energy and Mineral Resources Regulation No. 1 of 2008, the distribution of benefits from old oil well exploitation remains inequitable, with limited socio-economic impact on surrounding communities. This condition reflects a gap between legal norms and their implementation in practice. From the perspectives of maqāṣid al-sharīʿah and the Jurisprudence of Equitable Energy, the state and resource operators hold both moral and legal responsibilities to ensure justice (ʿadl), public welfare (maṣlaḥah), and the protection of essential human interests, including life (ḥifẓ al-nafs), property (ḥifẓ al-māl), and the environment (ḥifẓ al-biʾah). This study argues that strengthening legal frameworks and implementing community empowerment initiatives are crucial to addressing these disparities. Integrating Islamic ethical principles into energy governance is essential to fostering a more inclusive, sustainable, and equitable energy system that upholds human dignity and promotes meaningful local participation.